1988
DOI: 10.2957/kanzo.29.198
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ethanol on the sinusoidal endothelial fenestration of rat liver.

Abstract: The alterations of sinusoidal endothelial fenestration (SEF) were elucidated in rats liver acutely or chronically fed ethanol and after withdrawal of ethanol administration using scanning electron microscope. The liver sinusoids were perfused at 10 cmH2O pressure via portal vein and diameter, number and porosity of SEF were analysed morphometrically. There was heterogeneity in size and number of SEF in the hepatic lobule in control rats. In control rats, the diameter of SEF in zone 1 was significantly (p<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Ethanol feeding for 8 weeks decreased the number of fenestrations and increased the fenestration diameter, which was associated with a reduction in endothelial porosity in both the centrilobular and periportal sinusoids. The decreased porosities contrast the data reported by Kanaoka et al (1988) above but these changes are in accord with those found in human alcoholics and in alcohol‐fed baboons (Horn et al, 1987; Mak & Lieber, 1984). Interestingly, TEM showed there was marked endocytic activity associated with the sinusoidal endothelial cells after chronic ethanol consumption, which could be a factor leading to the reduced porosity.…”
Section: Chronic Ethanol Ingestion In Rats and Micesupporting
confidence: 87%
See 4 more Smart Citations
“…Ethanol feeding for 8 weeks decreased the number of fenestrations and increased the fenestration diameter, which was associated with a reduction in endothelial porosity in both the centrilobular and periportal sinusoids. The decreased porosities contrast the data reported by Kanaoka et al (1988) above but these changes are in accord with those found in human alcoholics and in alcohol‐fed baboons (Horn et al, 1987; Mak & Lieber, 1984). Interestingly, TEM showed there was marked endocytic activity associated with the sinusoidal endothelial cells after chronic ethanol consumption, which could be a factor leading to the reduced porosity.…”
Section: Chronic Ethanol Ingestion In Rats and Micesupporting
confidence: 87%
“…After 6 weeks of ethanol feeding, the endothelial porosity was higher in zone 3 in association with fewer fenestrations and an increased diameter of fenestrations. The findings are like those reported in rats by Kanaoka et al (1988), but the higher porosity data are dissimilar to the lower porosity data of Tanikawa et al (1991). The sinusoids in zone 3 appear to be tortuous and narrow, which is thought to be related to the ballooning of hepatocytes compressing the sinusoids.…”
Section: Chronic Ethanol Ingestion In Rats and Micesupporting
confidence: 81%
See 3 more Smart Citations